2013
DOI: 10.1051/0004-6361/201219423
|View full text |Cite
|
Sign up to set email alerts
|

Ionisation impact of high-mass stars on interstellar filaments

Abstract: Context. Ionising stars reshape their original molecular cloud and impact star formation, leading to spectacular morphologies such as bipolar nebulae around H ii regions. Molecular clouds are structured in filaments where stars principally form, as revealed by the Herschel space observatory. The prominent southern hemisphere H ii region, RCW 36, is one of these bipolar nebulae.Aims. We study the physical connection between the filamentary structures of the Vela C molecular cloud and the bipolar morphology of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 49 publications
5
62
0
Order By: Relevance
“…A strong feedback similar to the situation in the CNC has been found in the Herschel study of the RCW36 bipolar nebula in Vela C by Minier et al (2013).…”
Section: Relative Importance Of Massive Star Feedback and Primordial supporting
confidence: 74%
“…A strong feedback similar to the situation in the CNC has been found in the Herschel study of the RCW36 bipolar nebula in Vela C by Minier et al (2013).…”
Section: Relative Importance Of Massive Star Feedback and Primordial supporting
confidence: 74%
“…Towards the bipolar nebula around RCW 36 (Minier et al 2013), the ionization by the H ii region and the related increase in dust temperature can potentially introduce differences in the B ⊥ orientation across the BLASTPol wavelength bands. To test this, we evaluated the difference between the B ⊥ orientation inferred from the observations at different wavelengths in the region around RCW 36, where the dust temperature, derived from the Herschel observations, is larger than 20 K. The results, presented in the bottom panel of Fig.…”
Section: Notesmentioning
confidence: 99%
“…Such regions are observed within the HOBYS 1 key program (see Motte et al 2010Motte et al , 2012, and our study focuses on typical examples, i.e. the Rosette Schneider et al 2010b) and M 16 molecular clouds (Hill et al 2012b), and the H ii regions RCW 120 Anderson et al 2010Anderson et al , 2012 and RCW 36 (in the Vela C molecular cloud, Hill et al 2011;Minier et al 2013).…”
Section: Introductionmentioning
confidence: 95%
“…If the gravitational collapse had happened before, we would expect the exponent to be close to 2 and to be only marginally affected by the ionization since the ionizing front did not overwhelm the condensation. Indeed, the numerical study in Minier et al (2013) in the case of RCW 36 showed that the collapse of a condensation that is located in the shell is likely to be triggered. If the condensation had gravitationally collapsed prior to the passage of the ionization front, the condensation would already be dense enough to resist the ionization front expansion.…”
Section: Rcw 120mentioning
confidence: 99%